2020
DOI: 10.14782/marmarasbd.699422
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Variation of the Attitudes towards the Syrian Refugees in Turkey

Abstract: Is it possible to change the negative public attitudes towards refugees? Which factors reinforce such attitudinal changes? Since the refugee population is growing in many countries, finding answers to these questions has become even more important. By focusing on the Turkish context, this study has two specific objectives. First, we aim to find out how-and to what extent-the individual level of prejudice towards the Syrian refugees differs when the refugees are depicted in either empathy or threat-evoking cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…This study examines the attitudes of the host community toward Syrian refugees from the perspective of threats and opportunities. Quantitative studies in Turkey examine the attitudes of the host community towards Syrian refugees [30,[42][43][44][45] . However, it is observed that there is a limited number of qualitative studies that provide in-depth information on this topic in the literature (e.g., [46] ), and there is no study that examines attitudes towards Syrian refugees using the TFM.…”
Section: Discussionmentioning
confidence: 99%
“…This study examines the attitudes of the host community toward Syrian refugees from the perspective of threats and opportunities. Quantitative studies in Turkey examine the attitudes of the host community towards Syrian refugees [30,[42][43][44][45] . However, it is observed that there is a limited number of qualitative studies that provide in-depth information on this topic in the literature (e.g., [46] ), and there is no study that examines attitudes towards Syrian refugees using the TFM.…”
Section: Discussionmentioning
confidence: 99%